Children's Physical Activity Levels Following Participation in a Classroom-Based Physical Activity Curriculum - Tan Leng Goh; Chee Hoi Leong; Timothy A Brusseau; James Hannon (MDPI AG, 2019)
A classroom-based physical activity curriculum offers an opportunity for students to be active during the school day to combat declining physical activity levels among this population. The effects of classroom-based physical activity curriculum on children of different weight categories is relatively unknown. Therefore, the purpose of this study was to examine the differences in physical activity levels between male and female students, and between students of different weight categories following participation in a classroom-based physical activity curriculum intervention. A total of 210 3rd to 5th grade (age = 9.1 ± 0.1) students from one U.S. elementary school participated in a 4-week intervention. Students’ physical activity levels were measured using pedometers, quantified by step counts pre- and post-intervention. Results from the study indicated that students’ physical activity levels increased after participation in the intervention; male students’ physical activity levels were higher than female students. Additionally, there was an increase in physical activity levels regardless of weight categories, with students of healthy weight exhibiting the most increase following participation in the intervention. In view of the improvement of children’s physical activity levels following their participation in a classroom-based physical activity curriculum, it is recommended that training and resources be provided for teachers to easily implement the curriculum during the school day.